Implementation of Glucose-6-Phosphate Dehydrogenase (G6PD) testing for Plasmodium vivax case management, a mixed method study from Cambodia. - Sarah A Cassidy-Seyoum; Keoratha Chheng; Phal Chanpheakdey; Agnes Meershoek; Michelle S Hsiang; Lorenz von Seidlein; Rupam Tripura; Bipin Adhikari; Benedikt Ley; Ric N Price; Dysoley Lek; Nora Engel; et al. (Public Library of Science (PLoS), 2024)
Plasmodium vivax remains a challenge for malaria elimination since it forms dormant liver stages (hypnozoites) that can reactivate after initial infection. 8-aminoquinolone drugs kill hypnozoites but can cause severe hemolysis in individuals with Glucose-6-Phosphate Dehydrogenase (G6PD) deficiency. The STANDARD G6PD test (Biosensor) is a novel point-of-care diagnostic capable of identifying G6PD deficiency prior to treatment. In 2021, Cambodia implemented the Biosensor to facilitate radical cure treatment for vivax malaria. To assess the Biosensor's implementation after its national rollout, a mixed-methods study was conducted in eight districts across three provinces in Cambodia. Interviews, focus group discussions, and observations explored stakeholders' experiences with G6PD testing and factors influencing its implementation. Quantitative data illustrative of test implementation were gathered from routine surveillance forms and key proportions derived. Qualitative data were analyzed thematically. The main challenge to implementing G6PD testing was that only 49.2% (437/888) of eligible patients reached health centers for G6PD testing following malaria diagnosis by community health workers. Factors influencing this included road conditions and long distances to the health center, compounded by the cost of seeking further care and patients' perceptions of vivax malaria and its treatment. 93.9% (790/841) of eligible vivax malaria patients who successfully completed referral (429/434) and directly presented to the health center (360/407) were G6PD tested. Key enabling factors included the test's acceptability among health workers and their understanding of the rationale for testing. Only 36.5% (443/1213) of eligible vivax episodes appropriately received primaquine. 70.5% (165/234) of female patients and all children under 20 kilograms never received primaquine. Our findings suggest that access to radical cure requires robust infrastructure and income security, which would likely improve referral rates to health centers enabling access. Bringing treatment closer to patients, through community health workers and nuanced community engagement, would improve access to curative treatment of vivax malaria.